The Ovary - Leung, P. C. K.; Adashi, E. Y. (Academic Press, 2019)
The Ovary, Third Edition, includes more than 60% new material that highlights the clinical aspects of human ovarian functions. It covers advances in the areas of genomics, assisted reproductive technology, and cancer diagnosis and treatment. This updated edition synthesizes new information at the molecular, cellular and organismal levels, while also presenting modern ovarian physiology in a more understandable and comparative context. The book looks at ovarian function from a detailed molecular and cellular level that examines all phases of the ovarian lifecycle that places special emphasis on the pathophysiology of the human ovary, including ovarian carcinogenesis.